Statin-associated rhabdomyolysis triggered by drug–drug interaction with itraconazole. (7th September 2016) - Dybro, Anne Mette; Damkier, Per; Rasmussen, Torsten Bloch; Hellfritzsch, Maja
Abstract : A 47-year-old woman had been treated with high-dose simvastatin for several years. After systemic treatment with the antifungal agent itraconazole, she developed muscle pain and highly elevated levels of creatine kinase and myoglobin. Muscle biopsy was compatible with statin-associated rhabdomyolysis, probably caused by a drug–drug interaction between simvastatin and itraconazole. The patient made full recovery. Three commonly used statins—simvastatin, atorvastatin and lovastatin—are metabolised by the liver enzyme CYP3A4. Several potent inhibitors of this enzyme are known, for example, azole antifungal agents such as itraconazole and posaconazole. If antifungal treatment is indicated in a patient using a CYP3A4-metabolised statin, we recommend (1) topical administration of the antifungal agent if possible, (2) the use of a non-CYP3A4-inhibiting antifungal drug such as terbinafine or (3) temporary discontinuation of statin treatment.